Diffuse melanosis cutis in the setting of BRAFV600E mutant melanoma and treatment with targeted therapies. (27th August 2014) - Minocha, Rashi; Kefford, Richard; Uribe, Pablo; Sebaratnam, Deshan F; Fernández‐Peñas, Pablo
Abstract: Diffuse melanosis cutis (DMC) is a rare presentation of metastatic melanoma associated with a particularly guarded prognosis. We report a case of a 35‐year‐old man with BRAF V600E metastatic melanoma treated with dabrafenib (as well as ipilimumab and whole brain radiotherapy), who is alive, 25 months after the onset of his DMC. This is significantly longer than the reported mean survival of 4 months, highlighting the importance of BRAF mutation testing and the promising survival advantage of using targeted therapies compared with conventional chemotherapeutic regimens.